Requirements Framework for Personalized Real-Time Feedback in Interactive Agent-Based E-Learning Systems - Omoda-Onyait, Godfrey; Lubega, Jude T.; Maiga3, Gilbert (Springer, Berlin, Heidelberg., 2013)
E-learning systems at the market do not adequately support learning in a constructivist way because they do not adapt to the special needs and personal attributes of individual learners. Eliciting complete and correct requirements is a major challenge in personalized learning. Literature review and Interviews conducted with twenty lecturers helped in the design of questionnaires administered to three hundred second and third year students of Bachelor of Science Education and IT related courses from two universities in Uganda. Respondents were allowed to interact with two types of systems A that gave feedback at the end of each task and B at every stage during a learning process. The nine attributes used in the design of the questionnaire got the lowest response being 55.8% (feedback) and the highest 74.2% (Personalizing learning). These were used to design the basic requirements framework
Keywords: Agent-Based Approach; E-Learning Systems; Framework; Interactive and Real-Time Feedback